Overview of the institutional background of Carbon Capture, Utilization and Storage (CCU/S) technologies in the European Union - Kádár Krisztina (Conference in cooperation with the European Association for Comparative Economic Studies, 2025)
Nowadays, global climate change is an outstandingly important issue. In order to minimize its negative consequences, carbon dioxide (CO2) emissions and their atmospheric concentration must be reduced. Despite the ambient CO2 concentration being unprecedently high, it is a challenge to reduce it because the emissions are very diverse and there is no one-size-fits-all solution for them. The multifaceted problem thus requires multifaceted solutions, such as Carbon Capture, Utilization and Storage (CCU/S) technologies besides the other decarbonization tools. However, due to being an emerging technology, the appropriate regulatory and political background is still in its infancy, but these technologies are gaining more and more attention. The purpose of this review is to discuss the current institutional background of CCU/S technologies in the European Union (EU). By examining the critical points for CCU/S technologies to be deployed widespread, it can be seen that the EU considers these solutions to be of strategic value due to their future importance and relevance in climate change mitigation.